PELATIHAN PENULISAN ARTIKEL ILMIAH PKM BERBASIS AI PADA KELOMPOK KKN DIK - Ibrahim; Aryansyah; Sahrayani; Nadya Hayatul Iman; Lilis Suriani; Nuraini; Aan Juriati; Sirajul Hamdi; Muhammad Hanapi (AbdiMuh : Jurnal Pengabdian Masyarakat, 2025)
The scientific article writing skills of students participating in the Community Service Program (KKN Dik) are still considered low in terms of academic and digital literacy. The purpose of this activity was to improve the writing skills of AI-based Community Service Program articles among the KKN Dik group at MBS Selong High School, East Lombok. The method used in this community service program was a training activity with socialization and hands-on practice. The method was implemented in three stages: planning, implementation, and evaluation. The results and discussion indicate that the training using the ChatGPT and Mendeley tools improved participants' understanding of scientific article structure, their ability to use AI ethically, and their ability to produce publishable Community Service Program articles. The integration of AI into the writing training facilitated and increased students' confidence in the academic world. This training activity provided opportunities to produce high-quality scientific work in completing final reports during the Community Service Program.